2012
DOI: 10.1155/2012/529495
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of Dental Luting Agents: Potential to Hinder the Development of Secondary Caries

Abstract: A modified direct contact test was used to evaluate the antibacterial properties of four commercially available dental luting agents (RelyX Unicem, Ketac Cem, Ceramir Crown & Bridge and Harvard Cement) and two reference materials (glass-ionomer cement and calcium aluminate cement) compared to a negative-control material (PMMA). Streptococcus mutans bacteria were placed in direct contact with specimens that had been aged for 10 min, 1 day, and 7 days, in order to test the antibacterial properties of the materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Growth medium is then added and proliferation is monitored under further incubation, either continuously or after a certain time point. With materials and antibacterial mechanisms in this study being different from previous studies, [48][49][50] the critical parameter in the DCT was to establish a close contact between bacteria and substrate. This would enable a more precise evaluation of antibacterial properties at the surface, rather than in any volume above it.…”
Section: Methodsmentioning
confidence: 93%
“…Growth medium is then added and proliferation is monitored under further incubation, either continuously or after a certain time point. With materials and antibacterial mechanisms in this study being different from previous studies, [48][49][50] the critical parameter in the DCT was to establish a close contact between bacteria and substrate. This would enable a more precise evaluation of antibacterial properties at the surface, rather than in any volume above it.…”
Section: Methodsmentioning
confidence: 93%
“…However, incorporation of Ag-HA and Ag-DCPA had no effect on the release of F − . In addition, the amount of released F − was low and far less than the amount that can inhibit the bacteria proliferation [ 26 ]. Brajendra et al [ 27 ] have studied the Ag + release from Ca 10− x Ag x (PO 4 ) 6 (OH) 2 (0.2 ≤ x ≤ 0.5) and showed that x = 0.2 composition in phosphate buffer solution release no detectable Ag + and only small amount of Ag + (0.006 ppm and 0.004 ppm) can be detected in samples x = 0.3 and x = 0.5 after 72 h incubation.…”
Section: Discussionmentioning
confidence: 99%
“…19,20,[24][25] Different antibacterial agents have been used with Dentin bonding agents,Root canal irrigating solutions,Luting cement to affect antibacterial activity. Cetrimide is proven antibacterial agents 13,[26][27] .It has been used in different concentration to study their influence on antibacterial activity and other physical properties of luting cements. 28,29,[33][34] Cetrimide has reported to have positive influence on flexural strength and antibacterial activity of conventional luting cement.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from other properties, ideal luting agent should also possess antibacterial and anticariogenic properties.Luting agents like Zinc Phosphate,Zinc Polycarboxylate and Glass ionomer cements have antibacterial properties because of low ph and/or release of flouride but Resin cement does not exhibit significant antibacterial action. [5][6][7][8][9]13 Role of Cetrimide as antibacterial agent has been well documented. Cetrimide have been used in past in various concentrations to improve antimicrobial activity of Glass ionomer cements,Zinc Poycarboxylate cement ,Bonding agents and root canal irrigating solutions.…”
Section: Introductionmentioning
confidence: 99%